Avaliação da atividade antimicrobiana e análise morfológica por microscopia de força atômica (AFM) da ação de extratos de própolis verde sobre Staphylococcus aureus e Escherichia coli - Campos, Jessica Valéria De (2017)
In the last years the concerns about the resistance acquired by pathogenic microorganisms has increased due to large misuse of antibiotics and agricultural products. Research about new alternatives and natural antimicrobial agents allows, at least, a partial replacement of synthetic drugs. The interest in studying the biological activities of propolis has gained importance due to its great antimicrobial potential, which is attributed to phenolic compounds, especially to the flavonoids. In this sense, the propolis appears as an important therapeutic alternative. The antimicrobial action of this resin has been confirmed in several studies; however, an analysis of the mechanism of action is still scarce. Thus, to identify the presence of antibacterial constituents along with the analyzes by atomic force microscope (AFM), that allows evaluating modifications of the bacterial structures treated with propolis extract, were the main aims of this work. Extracts with different proportions of water and ethanol were prepared and simultaneously processed following standards. The extracts were characterized related to their composition and antibacterial property against Gram-positive Staphylococcus aureus and Gram-negative Escherichia coli bacteria. It was observed that the use of higher concentrations of ethanol in the extract production provided higher extractions of flavonoids and better antibacterial effects. Thus, the best results were attained by the ethanolic extract of propolis, composed of 100% ethanol (EEP), and conversely, the less efficient extract, composed of lower concentrations of flavonoids, was the aqueous one (EAP). The results obtained in the analyzes in FTIR and HPLC confirm a greater presence of flavonoids in the extracts with higher levels of ethanol. Regarding the microscopic analysis, the EEP was selected for analysis considering its better antibacterial capacity. For a satisfactory inhibition of the E. coli growth a more concentrated extract was necessary, leading to an increase in cell volume, and a probable occurrence of bacteriolysis and the occurrence of cellular damages. In general, the propolis showed to have action on the cellular structure of both bacteria, leading to inhibition of microbial growth.